Timing differences in the generation of ground reaction forces between the initial and secondary landing phases of the drop vertical jump - Bates, Nathaniel A. (2013)
BACKGROUND: Rapid impulse loads imparted on the lower extremity from ground contact when landing from a jump may contribute to ACL injury prevalence in female athletes. The drop jump and drop landing tasks enacted in the first and second landings of drop vertical jumps, respectively, have been shown to elicit separate neuromechanical responses. We examined the first and second landings of a drop vertical jump for differences in landing phase duration, time to peak force, and rate of force development. METHODS: 239 adolescent female basketball players completed drop vertical jumps from an initial height of 31 cm. In-ground force platforms and a three dimensional motion capture system recorded force and positional data for each trial. FINDINGS: Between the first and second landing, rate of force development experienced no change (P > 0.62), landing phase duration decreased (P = 0.01), and time to peak ground reaction force increased (P < 0.01). Side-by-side asymmetry in rate of force development was not present in either landing (P > 0.12). INTERPRETATION: The current results have important implications for the future assessment of ACL injury risk behaviors. Rate of force development remained unchanged between first and second landings from equivalent fall height, while time to peak reaction force increased during the second landing. Neither factor was dependent on the total time duration of landing phase, which decreased during the second landing. Shorter time to peak force may increase ligament strain and better represent the abrupt joint loading that is associated with ACL injury risk.